The pirates of Crocodile Swamp - Arnosky, Jim (G.P. Putnam's Sons, 2009)
Brothers Sandy and Jack Casperin flee from their abusive father into the remote swamplands of the Florida Keys, and after they learn how to survive on their own amongst the dangerous wildlife, they encounter a young girl and an old sailor who teach them how to begin anew.